Local government principles and practice : a text for risk managers - Watt, Peter A.; Institute of Risk Management (London : Witherby & Co. Ltd., 1996)
This book provides an up-to-date account of local government in Britain. It is also valuable to general readers seeking an overview of the current principles and practice of British local government.
Includes bibliographical references and index.
osa; 01/11/2016
Loans
Keywords: Local government .; Local government studies; Local government - finance